Marriage Confirmation: Secret Marriage And Division Of Joint Assets - Muhammad Adami (AT-TAFAHUM: Journal of Law, 2017)
One of the consequences of divorce from a sirri marriage or underhand marriage is related to the wife's share of the joint property. This is because in a sirri marriage or underhand marriage there are no provisions regarding the division of joint property. Provisions regarding the division of joint property are only regulated in registered marriages as stipulated in the Compilation of Islamic Law, Article 7, number 3 letter (a), that marriage confirmation provides a way for the interests of husbands and wives who have had a sirri or underhand marriage to be registered under state law. From an empirical legal perspective, the 120 people who participated in the marriage confirmation hearing on April 21, 2017, which was first held in Hamparan Perak sub-district, Deli Serdang, are proof that the community believes that marriage confirmation is the best solution.